IMPACT OF EVOLVING TECHNOLOGY AND TRANSFORMING DEMOGRAPHY ON CONSUMER BEHAVIOUR - Udagi, Kanyakumari; Huggi, Meenakshi M; Bhuwaneshwari R (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid advancements in technology and changing demographic structures significantly impact consumer behaviour. This article explores how technological innovations and demographic transitions influence purchase decisions, preferences, and brand loyalty among consumers. By leveraging data from various surveys, market studies, and consumer analytics, this paper examines the extent of these influences. The study also highlights strategies for businesses to adapt to these changing dynamics to remain competitive in a highly globalized market.